Hip Abductor Muscle Fatigue Induces Different Strategies During Disrupted Postural Control - Dury, Jeanne; Ravier, Gilles; Michel, Fabrice (Frontiers in Sports and Active Living, 2022)
Background Ankle sprain is one of the most common injuries in sport, and hip abductor muscle weakness has recently been reported as a predisposing factor. Currently, the influence of hip abductor muscle fatigue on ankle joint control has not been elucidated during an ankle disturbed balance exercise. This study aimed to determine the influence of hip abductor muscle fatigue on ankle joint control during a disturbed balance task, and to consider inter-individual variability in the kinematic and neuromuscular reorganizations implemented. Methods Twenty-six healthy subjects (13 males; 13 females) performed a unipedal postural balance task with eyes closed before and after a fatiguing exercise (up to a 50% decrease in strength) of the hip abductor muscles. Subjects completed balance task while equipped with an ankle destabilization device that allows inversion/eversion movements. Electromyographic (EMG) activity of the gastrocnemius lateralis (GastL), peroneus longus (PL) and brevis, tibialis anterior, and gluteus medius were recorded during task. Kinematics (e.g., frontal foot angulation) of the ankle complex were determined using inertial measurement units. Results In the overall group, no significant time, sex or interaction effect was observed for kinematic and EMG variables. However, when considering individual responses to hip fatigue, 14 subjects decreased the standard deviation of frontal angulation (−30%) suggesting enhancement of ankle joint control, while 12 subjects increased it (+46%). Normalized EMG for PL and GastL muscles changed with fatigue for both these groups. However, variations were significantly different between groups (p = 0.027 for PL and p = 0.006 for GastL). Indeed, the contribution of ankle muscles increased for the enhanced-stability group while no change for the impaired-stability group. Conclusion These results highlight that subject adopt different neuromuscular and kinematic ankle strategies to control ankle destabilization in response to hip abductor muscle fatigue. Frontal foot angulation variability seemed to be a valuable marker to detect the type of strategy employed. The strategy adopted by the impaired-stability group might have important implications when analyzing risk factors for ankle sprains. Further studies should consider individual responses to fatigue, to understand which factor could predispose athletes to use of one or other strategy.